SAT0458 Identification of genetic variation specifically associated with psoriatic arthritis using genome-wide association studies. (15th June 2017) - Cañete, JD; Aterido, A; Pinto, JA; Gratacόs, J; Queirό, R; Montilla, C; Torre-Alonso, JC; Pérez-Venegas, JJ; Fernández-Nebro, A; Muñoz-Fernández, S; González, C; Roig, D; et al.
Abstract : Background: PsA has a higher heritability than PsV, indicating the existence of additional PsA-specific genetic factors. To date, however, the specific genetic basis underlying PsA is poorly understood. Objectives: The objective the present study was to identify new genetic variation specifically associated with PsA risk. Methods: In order to characterize the genetic basis of PsA, we performed a GWAS meta-analysis at the single-marker level as well as at the pathway level (GWPA). A cohort of 835 PsA patients and 1, 558 controls from the Spanish population was genotyped for >550, 000 SNPs. GWAS data from a second cohort of 1, 430 PsA patients and 1, 417 controls from the North American population was also used. In order to confirm the specificity of the new genetic variation associated with PsA risk, we analyzed the association with purely cutaneous psoriasis (PsC, n=614) and rheumatoid arthritis (RA, n=1, 191). We performed a pharmacogenetic analysis to investigate the new PsA-specific pathways as a source for drug discovery in PsA. Results: GWAS meta-analysis identified a new association between B3GNT2 gene and PsA ( P <5e-08). In the GWAS pathway analysis, we identified and validated a total of 14 genetic pathways associated with PsA risk. From these, the glycosaminoglycan (GAG) metabolism pathway was also found to be significantly associated with PsA risk when directly contrasted to the PsC cohort as well as the RA cohort. At the functional level, we detected a significant differential expression of GAG metabolism pathway genes in blood samples from PsA patients compared to PsC patients. The pharmacogenetic analysis identified several FDA-approved drugs likely to modify the GAG pathway. Conclusions: The present study represents an important step towards the characterization of the genetic factors specific to PsA risk. Disclosure of Interest: None declared